Analysis of the Dose-Response Effects of Physical Activity on Cardiocerebrovascular and All-Cause Mortality in Hypertension - Xu, Jun-Peng; Zeng, Rui-Xiang; Lu, Hai-Ning; Zhang, Yu-Zhuo; Mai, Xiao-Yi; Mao, Shuai; Zhang, Min-Zhou (Frontiers in Cardiovascular Medicine, 2022)
Background Leisure-time moderate-to-vigorous physical activity (MV-PA) has been consistently regarded as a protective factor to prevent and treat hypertension. However, the effect of different levels of MV-PA against cardiocerebrovascular and all-cause mortality in hypertension is still unclear. The aim of this study was to explore the dose relationships of MV-PA on these adverse outcomes in hypertension. Methods In the National Health and Nutritional Examination Survey (NHANES) from 1999 to 2006, participants with hypertension were enrolled and classified into inactive (0 MET-h/week), low-active (0 < to < 7.5 MET-h/week), and high-active (≥ 7.5 MET-h/week) groups. A multivariate Cox regression analysis was conducted with a hazard ratio (HR) and corresponding 95% confidence interval (CI). To further explore the association between different levels of MV-PA and adverse outcomes, Kaplan-Meier survival curves, subgroup analysis, and restricted cubic spline curves were performed. Results During a median 10.93-year follow-up, 1,510 and 347 patients had died from any causes and cardiocerebrovascular, respectively. The high-active group had the highest event-free survivals of all outcomes compared with low-active and inactive groups. A multivariate Cox regression analysis demonstrated that the high-active and low-active groups were associated with reduced risks of all-cause [HR: 0.70, 95% CI: 0.60–0.82; 0.76 (0.68–0.86), respectively] and cardiocerebrovascular mortality [0.56 (0.41–0.77); 0.63 (0.50–0.81), respectively] compared with the inactive group. Subgroup analysis and restricted cubic spline curves showed that MV-PA surpassing 15 MET-h/week could decrease the risks of cardiovascular and all-cause mortality with inverse relationships, which was not the case for cerebrovascular mortality, indicating a U-shaped association. Conclusion Our study suggests that highly active MV-PA of 7.5 to < 15 MET-h/week was associated with the lowest risks of cardiocerebrovascular and all-cause mortality in hypertension.